PENGARUH MODAL AWAL, LAMA USAHA, JAM KERJA DAN JUMLAH TENAGA KERJA TERHADAP PENDAPATAN PEDAGANG TOKO PAKAIAN DI KECAMATAN UNAAHA - Heriswanto1* Liswatin (FEB Universitas Lakidende, 2019)
The purpose of this study was to determine the Effect of Initial Capital, Length of Business, Hours of Work and Number of Labor Against the Income of Clothing Store Traders in Unaaha District. The population in this study is the owner of a clothing store in Unaaha District obtained through porpose sampling technique with certain criteria. Data collection methods by interview and questionnaire, and analyzed using multiple linear regression analysis The results of this study indicate that simultaneously Initial Capital, Length of Business, Hours of Work and Number of Workers have a positive and significant effect on merchant income, partially Initial Capital has a positive and significant effect on merchant income, Business Length has a positive and significant effect on trader income, Hours Work does not affect the income of traders and the number of labor does not affect the income of traders. R squere value of 0.668 which means that the variable Initial Capital, Length of Business, Hours of Work and Number of Workers is only able to explain the variable income of traders by 66.8% and the remaining 33.2% is explained by c = other variables outside this study.